Characterisation of residual char from biomass gasification: effect of the gasifier operating conditions. (1st December 2016) - Hernández, Juan J.; Lapuerta, Magín; Monedero, Esperanza
Abstract: Char, together with tars, are the main wastes derived from biomass gasification. The removal of tars and the valorisation of char are necessary to avoid technical problems and to increase the overall efficiency of the gasification plant, respectively (both aspects encouraging the commercial implementation of biomass gasification systems). However, char properties may not be suitable for an easy valorisation. This work analyses the effect of the main gasifier operating conditions (relative biomass/air ratio, temperature and steam content of the gasifying agent) on the properties of char produced from gasification of dealcoholised marc of grape. Those properties allow both, to analyse the phenomena taking place during the conversion process and to assess potential applications (valorisation) of this waste. Gasification was carried out in a small-scale drop-tube pilot plant. Char characterisation includes structural, thermo-chemical and compositional analysis. Results show that an increase of the relative biomass/air ratio leads to a higher char production as well as to an increase in the extent of the carbonisation, which makes the char more aromatic and stable. Intermediate relative biomass/air ratios (∼3.5), indicate a trade-off between fuel conversion and char specific surface area. On the other hand, higher operating temperatures lead to a less reactive char as a consequence of a higher fuel conversion. All obtained chars have low specific surface area (<70 g/m 2 ), which discourages their application as activated carbon without further activation. Inorganic elements have in general a high retention level in the carbonaceous matrix (∼70–80% for most compounds), which decreases at higher temperatures and/or lower steam content in the gasifying agent. The char could also be recirculated to the gasifier or to a combustor. However, the alkali index values of both the initial biomass and the gasification chars are far above the limit considered as troublesome, thus being likely to cause slagging and fouling problems.